Overview of Knowledge of Couples of Childbearing Age Signs of Pregnancy in Nagori, Bandar Malaka District, Gunung Maligas District, Simalungun Regency - Santi Widya Purba; Sri Rahma Friani; Dini Pajriani Khairunnisa (Jurnal EduHealth, 2025)
Not all couples of childbearing age (PUS), have healthy reproduction in the sense of having fertility that is ready to be fertilized or fertilized. To overcome this, most PUS choose to have children through artificial conception. Based on the rules that apply in Indonesia, namely Law No. 32 of 1992 concerning Health article 16 paragraphs 1 and 2 and Law No. 39 of 1999 concerning Human Rights article 10 paragraph 1, only artificial conception through a legal marriage is allowed. So that artificial conceptions through sperm donors of other people who are not legally married are unlawful acts and contrary to the human rights that apply in Indonesia.From the results of the study with the title "Overview of PUS Knowledge About the Signs of Pregnancy in Nagori Bandar Malaka Kec. knowledgeable Less than 22 people (63%). Based on the age, the majority of respondents aged 19-24 years have less knowledge than 12 people (54.54%). Based on the source of information, the majority of respondents who received information sources from friends were 9 respondents (40.90%). Based on the parity, the majority of respondents who are knowledgeable Less at parity >1 person as many as 12 respondents (54.54%). Based on education, the majority of people (90.90%) are in elementary education with less knowledge. It is recommended that pus further increase his knowledge about the signs of pregnancy by reading a lot about information sources. It is expected that health workers will provide more health counseling about the signs of pregnancy so that they know what are the signs of pregnancy.